Autosomal recessive hypotrichosis with loose anagen hairs associated with TKFC mutations. (2nd November 2020) - Onoufriadis, A.; Cabezas, A.; Ng, J.C.F.; Canales, J.; Costas, M.J.; Ribeiro, J.M.; Rodrigues, J.R.; McAleer, M.A.; Castelo‐Soccio, L.; Simpson, M.A.; Fraternali, F.; Irvine, A.D.; et al.
Summary: Background: Loose anagen hair is a rare form of impaired hair anchorage in which anagen hairs that lack inner and outer root sheaths can be gently and painlessly plucked from the scalp. This condition usually occurs in children and is often self‐limiting. A genetic basis for the disorder has been suggested but not proven. A better understanding the aetiology of loose anagen hair may improve prevention and treatment strategies. Objectives: To identify a possible genetic basis of loose anagen hair using next‐generation DNA sequencing and functional analysis of variants identified. Methods: In this case study, whole‐exome sequencing analysis of a pedigree with one affected individual with features of loose anagen hair was performed. Results: The patient was found to be compound heterozygous for two single‐nucleotide substitutions in TKFC resulting in the following missense mutations: c.574G> C (p.Gly192Arg) and c.682C> T (p.Arg228Trp). Structural analysis of human TKFC showed that both mutations are located near the active site cavity. Kinetic assays of recombinant proteins bearing either of these amino acid substitutions showed almost no dihydroxyacetone kinase or D‐glyceraldehyde kinase activity, and FMN cyclase activity reduced to just 10% of wildtype catalytic activity. Conclusions: TKFC missense mutations may predispose to the development of loose anagen hairs. Identification of this new biochemical pathobiology expands the metabolic and genetic basis of hypotrichosis. Abstract : What is already known about the topic? Loose anagen hair syndrome is a rare condition with an estimated incidence of two cases per million per year, mainly observed in female children aged between 2 years and 6 years. Loose anagen hairs are loosely anchored and can be easily plucked from the scalp. To date, no gene pathology has been associated with loose anagen syndrome. What does this study add? By undertaking whole‐exome sequencing in an individual with loose anagen hairs, and in other unaffected family members, we identified compound heterozygosity for missense mutations in TKFC . Functional analysis of both amino acid variants showed defective catalytic activity implicating TKFC in hair cycling and structural maintenance. The identification of TKFC mutations expands the molecular basis of hypotrichosis and provides a new biochemical target for potential therapeutic intervention. What is the translational message? DNA variants in many different genes, including TKFC, contribute to hypotrichosis. Defining individual gene pathology provides more precise mechanistic insights into the diverse aetiology of inherited forms of hypotrichosis and a basis to develop personalized medicine to improve hair growth. Linked Comment: Brown. Br J Dermatol 2021; 184 :800–801 .